Antenna beam pattern modelling for sky-averaged 21 cm cosmology experiments - Pieterse, Carla Maria (Stellenbosch : Stellenbosch University, 2025)
Pieterse, C. M. 2025. Antenna Beam Pattern Modelling for Sky-Averaged 21 cm Cosmology Experiments. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/96772db0-0099-4d73-885b-ef453a8bb8df